1990
DOI: 10.2307/2393393
|View full text |Cite
|
Sign up to set email alerts
|

Champions of Technological Innovation

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. This study investigated the personality characteristics, leadership behaviors, and influence tactics of champions of technological innovations. Analyses of questionnaires and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
808
1
7

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,105 publications
(832 citation statements)
references
References 43 publications
16
808
1
7
Order By: Relevance
“…The need for product champions is widely recognised (Kanter, 1988;Peters and Waterman, 1982;Pinchot, 1985), and their contribution to successful innovation has been widely reported (Frost and Egri, 1991;Howell and Higgins, 1990). Two thirds of the firms surveyed by Duchesneau (1977) confirmed the presence of such a role, and the SAPPHO project of the 1970s provided systematic evidence to support the product champion hypothesis (Achilladelis et al, 1971).…”
Section: 'A Member Of An Organisation Who Creates Defines and Adoptsmentioning
confidence: 99%
“…The need for product champions is widely recognised (Kanter, 1988;Peters and Waterman, 1982;Pinchot, 1985), and their contribution to successful innovation has been widely reported (Frost and Egri, 1991;Howell and Higgins, 1990). Two thirds of the firms surveyed by Duchesneau (1977) confirmed the presence of such a role, and the SAPPHO project of the 1970s provided systematic evidence to support the product champion hypothesis (Achilladelis et al, 1971).…”
Section: 'A Member Of An Organisation Who Creates Defines and Adoptsmentioning
confidence: 99%
“…Research shows that transformational leaders put greater emphasis on innovation than transactional leaders (Church & Waclawski, 1998;Howell & Higgins, 1990). In addition, recent research found a positive relationship between transformational leadership and organizational innovation (Gumusluoglu & Ilsev, 2009;Jung, Chow, & Wu, 2003;Jung, Wu, & Chow, 2008).…”
Section: Transformational and Transactional Leadership And Innovativementioning
confidence: 99%
“…Even with here-and-now, small-scale expectations and interactions, participants confront what can be called differing "readiness factors" (Olson & Olson, 2000). The introduction of technology is discussed in the champion literature with leadership depending upon different types of goals, champions (e.g., project, technical, and user champions), and innovators (e.g., gatekeepers focused on products in particular and conceptualists focused on approaches) (Howell & Higgins, 1990;Schon, 1963). In planning for the internet, there is a shifting baseline of understanding as the user/designer base of experience grows.…”
Section: Infrastructure In Timementioning
confidence: 99%